Nystatin-Resistant Mutants of Yeast: Alterations in Sterol Content - Woods, Robin A. (J Bacteriol, 1971)
Mutants of the genes nys1 and nys3 differ from sensitive strains (nys(+)) in their sterol content. Ultraviolet absorption spectra of the nonsaponifiable material extracted from cells of nys(+) demonstrated the presence of ergosterol and 24(28)-dehydroergosterol. In nys1 mutants, the spectrum suggests the presence of a new sterol. The absorption spectrum of extracts from nys3 mutants indicates absence of both ergosterol and 24(28)-dehydroergosterol and presence of another new sterol. Conversion of nys(+) and nys3 to petite results in loss of 24(28)-dehydroergosterol in the former and the new sterol in the latter, whereas the new sterol in nys1 is only reduced. The sterols in ethanol-grown cells of all genotypes are essentially the same as is found for growth on glucose. With the exception of nys3 grown on ethanol, the mutants do not appear to be at a disadvantage compared to wild type.